2014
DOI: 10.1038/ncb3024
|View full text |Cite
|
Sign up to set email alerts
|

Early lineage restriction in temporally distinct populations of Mesp1 progenitors during mammalian heart development

Abstract: Cardiac development arises from two sources of mesoderm progenitors, the first heart field (FHF) and the second (SHF). Mesp1 has been proposed to mark the most primitive multipotent cardiac progenitors common for both heart fields. Here, using clonal analysis of the earliest prospective cardiovascular progenitors in a temporally controlled manner during early gastrulation, we found that Mesp1 progenitors consist of two temporally distinct pools of progenitors restricted to either the FHF or the SHF. FHF progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
317
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(354 citation statements)
references
References 71 publications
35
317
1
1
Order By: Relevance
“…Collectively, these observations suggest that only the most anterior subset of cardiac progenitors require Id1-4 activity for their specification. Consistent with our findings, Lescroart et al (2014) have shown recently that early Mesp1-expressing mesoderm progenitors (around E6.5), which contribute to first heart field derivatives, express high levels of Id1. In contrast, late Mesp1-expressing cells (around E7.5), which contribute to second heart field derivatives, express low levels of Id1 (see the Supplemental Material of Lescroart et al 2014).…”
Section: Molecular Control Of Cardiogenic Mesoderm Specificationsupporting
confidence: 80%
See 1 more Smart Citation
“…Collectively, these observations suggest that only the most anterior subset of cardiac progenitors require Id1-4 activity for their specification. Consistent with our findings, Lescroart et al (2014) have shown recently that early Mesp1-expressing mesoderm progenitors (around E6.5), which contribute to first heart field derivatives, express high levels of Id1. In contrast, late Mesp1-expressing cells (around E7.5), which contribute to second heart field derivatives, express low levels of Id1 (see the Supplemental Material of Lescroart et al 2014).…”
Section: Molecular Control Of Cardiogenic Mesoderm Specificationsupporting
confidence: 80%
“…Consistent with our findings, Lescroart et al (2014) have shown recently that early Mesp1-expressing mesoderm progenitors (around E6.5), which contribute to first heart field derivatives, express high levels of Id1. In contrast, late Mesp1-expressing cells (around E7.5), which contribute to second heart field derivatives, express low levels of Id1 (see the Supplemental Material of Lescroart et al 2014). Moreover, we show that human iMPs upregulate first heart field markers (HCN4 and TBX5) during cardiac differentiation, while second heart field markers (ISL1 and SIX2) are down-regulated (Supplemental Fig.…”
Section: Molecular Control Of Cardiogenic Mesoderm Specificationsupporting
confidence: 80%
“…2D,E, arrows). These new progenitors have their origins in a distinct heart progenitor field termed the second heart field (SHF), which probably exits the primitive streak somewhat later than FHF progenitors (Lescroart et al, 2014). SHF cells are therefore delayed in their differentiation.…”
Section: The Origin Of Cardiac Lineages In Developmentmentioning
confidence: 99%
“…However, recent lineage-tracing studies have shown that although FHF and SHF cells arise from a common progenitor, probably in the pre-gastrulation embryo, their territories become geographically separate (Ali et al, 2014;Buckingham et al, 2005;Meilhac et al, 2004). FHF progenitors that form the primary heart tube and future left ventricle (Buckingham et al, 2005;Lescroart et al, 2014) are unipotent for cardiomyocytes or endothelial cell fates (Cohen-Gould and Mikawa, 1996;Lescroart et al, 2014). By contrast, SHF cells exiting the primitive streak later and contributing to other regions of the heart are either unipotent or bipotent for cardiomyocyte and endothelial cells, or cardiomyocytes and smooth muscle cells.…”
Section: The Origin Of Cardiac Lineages In Developmentmentioning
confidence: 99%
See 1 more Smart Citation